The Effect Of International Trade And Exchange Rates On Indonesia's Economic Growth In The Agricultural Sector For The 2019-2023 Period - Sari, Devi Anita; Fadillah, Luthfi Nur; Perwito, Perwito (JURNAL MANAJEMEN DAN BISNIS, 2025)
This study aims to analyze the effect of international trade, which is focused on agricultural exports, as well as the effect of exchange rates on economic growth in the period 2019 - 2023. The method used is quantitative associative method with multiple linear regression approach, using secondary data obtained from the Central Bureau of Statistics (BPS), Bank Indonesia (BI) and other sources. The collected data were analyzed using SPSS software, and tested using the classical assumption test to ensure the accuracy of the model. The results showed that agricultural exports and exchange rates had no significant effect on economic growth. Overall, the variables studied do not explain all the factors that influence economic growth, so there are other factors that are not discussed in this study. It could be inferred that while the exchange rate has a negative impact on the dependent variable, agricultural exports have a favorable impact on economic growth.